2011
DOI: 10.1016/j.limno.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Variability of phytoplankton biomass in a lowland river: Response to climate conditions

Abstract: a b s t r a c tThe results are presented of an intensive study of phytoplankton assemblage carried out in the Berounka River above its confluence with the Vltava River (Czech Republic) in the period 2002-2007. The annual and interannual changes of phytoplankton development (based on high frequency of sampling) and their relation to hydrological conditions and concentrations of main nutrients are analysed. A marked decline of nutrient concentrations was observed during the period 1996-2007. The annual mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…Significant reductions in chlorophyll concentrations (an indicator of phytoplankton biomass) have been observed following reductions in phosphorus concentrations of the River Rhine in The Netherlands and the Sacramento and San Joaquin rivers in California, USA (Van Nieuwenhuyse, 2007), which supports the hypothesis that phosphorus concentration is the key control of phytoplankton biomass. Conversely, other studies have shown little relationship between river nutrient concentration and either phytoplankton or periphyton biomass (Bernhardt and Likens, 2004;Figueroa-Nieves et al, 2006;Lewis and McCutchan, 2010;Royer et al, 2008;Yang et al, 2008), and reductions in river phosphorus concentrations in recent years have not resulted in the expected reduction in chlorophyll concentrations (Desortova and Puncochar, 2011;Neal et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Significant reductions in chlorophyll concentrations (an indicator of phytoplankton biomass) have been observed following reductions in phosphorus concentrations of the River Rhine in The Netherlands and the Sacramento and San Joaquin rivers in California, USA (Van Nieuwenhuyse, 2007), which supports the hypothesis that phosphorus concentration is the key control of phytoplankton biomass. Conversely, other studies have shown little relationship between river nutrient concentration and either phytoplankton or periphyton biomass (Bernhardt and Likens, 2004;Figueroa-Nieves et al, 2006;Lewis and McCutchan, 2010;Royer et al, 2008;Yang et al, 2008), and reductions in river phosphorus concentrations in recent years have not resulted in the expected reduction in chlorophyll concentrations (Desortova and Puncochar, 2011;Neal et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Only two sources of climatic disturbance, or climatic stressors, were employed in this study, both uniform through the year: change in precipitation and in air temperature. This strategy was adopted because it was recognised that temperature and residence time (strictly dependent on water discharge, and thus on precipitation) are the likely to be the most significant factors affecting phytoplankton concentrations and composition, as widely recognised in literature (Garnier et al, 1995;Reynolds, 2000;Desortová and Punčochář, 2011;Bowes et al, 2012). Nevertheless, other sources of climatic alteration may be relevant for the purpose of this study.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
“…Whether climate or nutrients have a stronger impact on plankton phenologies is a question that has not yet been answered: emerging evidence exists for either cases (Thackeray et al, 2008;Feuchtmayr et al, 2010;Desortová and Puncochár, 2011;Shimoda et al, 2011;Sipkay et al, 2012;Zhang et al, 2012).…”
Section: Quantitative Data Of Phenology Shift and Possible Drivers Bementioning
confidence: 99%